SYK kinase mediates brown fat differentiation and activation - Marko Knoll (Nature Portfolio, 2017)
Spleen protein tyrosine kinase (Syk) has so far been mainly studied in haematopoietic and immune cells. Here, the authors show that Syk also has a role in brown adipose tissue, where it regulates the formation of brown adipocytes and their thermogenic activation in response to β-adrenergic stimulation.